Narrowband Red-Sensitive Positive−Negative Reversible Photodetector Using Organic Dye on the TiO2/SnO2 Heterojunction - Suman S.; Pandey U.; Pal N.; Swaminathan P.; Pal B.N. (My University, 2025)
A narrowband red-sensitive negative photodetector is fabricated on a TiO2/SnO2 heterojunction by a solution-processed technique. The negative photoconductance of the device originates from the TiO2/SnO2 heterojunction and is converted into a narrowband red-sensitive photodetector by coating it with an organic dye, absorbing predominantly in the red portion of the visible spectrum. However, this negative red-sensitive photoresponse of the device can be converted to a positive photoresponse in a reversible manner by passing hot dry air. The negative photoconductance effect in the TiO2/SnO2 heterostructure is found to be persistent, whereas the positive photoconductance effect is characterized by its transient nature, indicating that the adsorbed H2O molecule on TiO2 has a key role in this negative photoconductivity. The photodetector exhibits a responsivity of 1.19 A/W and a detectivity of 6.0 × 1011 Jones to red-light illumination (650 nm, 12.5 W/m2) in positive photoconductance mode. Moreover, the nature of the photoresponse in positive and negative photoconductance behavior is quite different, which helps to identify the origin of the negative photoconductance of the device. © 2023 American Chemical Society.